OTA-based electronically tunable elliptic high-order current-mode ladder band-pass filter - Wongprommoon, Natapong; Prommee, Pipat (My University, 2014)
This paper presents Elliptic high-order currentmode ladder band-pass filter based on OTA-C that can be operated in high frequency. High-order band pass filter is designed based on Elliptic Ladder band-pass filter prototype. The proposed filter contains lossy and lossless integrators. The frequency responses of band-pass filter can be electronically tuned between around 100kHz and 10MHz by adjusting bias current form 0.15 μA to 1500 μA with 7.74mW of dynamic power consumption along tuning the bias current. The circuit used 1.5 V power supply and used of ground capacitors which suit to integrated circuit. THD of band-pass filter can be obtained less than 1% along the operating frequencies. PSPICE simulation results are carried out to confirm the theory by using TSMC 0.18μm CMOS technology.
Keywords: Band-pass; Elliptic; High-order; OTA-C